COMPARING TWO ANALYTICAL MODELS FOR ORBIT DETERMINATION USING GPS NAVIGATION SOLUTIONS (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work presents the results of two analytical orbit models for orbit determination using the navigation solutions provided by on-board GPS receivers. Herein one proposes to analyze two analytical orbit models that can be used both on-board and on ground control centers for quick orbit determination. One model is the NORAD SGP8 elements (Hoots andRoehrich, 1980) where the two-line elements (TLE) are the orbit data needed to compute orbits. The second one is the analytical orbit model of the CBERS (China-Brazil Earth Resources Satellite) mission named COE (CBERS Orbit Elements). The orbit determination (OD) system to generate the TLE and COE datasets is being developed to be implemented in the INPE (Brazilian Institute for Space Research) ground control center. The TLE may be disseminated regularly to allow image receiving ground stations to track the CBERS-4satellite. The COE can be used in the control center to monitor the orbit and compute maintenance maneuvers. The paper describes the basics of the two models, and implements such models to fit in the least squares sense the GPS long arc navigation solution measurements. Results will be shown based on actual GPS measurements from CBERS satellites, comparing aspects of the fittings and the models propagation.  Keywords: Orbit determination, GPS Navigation Solution, CBERS Orbit Elements, Two-Line Elements